Centro-dia para pessoas idosas: implantação versus ordenamento legal - Hara, Cláudio Hissashi (2016)
The theme “elderly” is a reality that is attracting the attention of various sectors of society in Brazil and worldwide. The debate on aging has led to reflection on the social risk that arises from the need for frequent and prolonged care provision for the elderly in situations of dependency. In Brazil, is no different. The country is heading towards becoming the sixth population of older people begin to demand specialized care; concurrently, we face the reduction of potential family caregivers in line with changes in the configuration and dynamics of families. It highlights the service in Day-Care as a social-service alternative needed to provide social protection of older people with dependency. The aim of this study is to demonstrate the precision difficulty of Day-Care concept from the requirements of the Federal Union, states and municipalities. We intend to address security/legal uncertainty of the concept, namely, a certain flexibility that may cause a adaptability situation, at the same time, traces a few clear guidelines for those facing the reality implementation. We conducted a survey of laws, ordinances, resolutions and national decrees through available on the internet data research, as well as articles published in journals and conference proceedings. It was possible to learn the various definitions found on the effectiveness of the inclusion criteria for the Day-Care. It is important to resume the discussion around what is provided in constitution and what is actually achieved, especially when the reference is social or fundamental rights. Effectiveness is the quality that has the standard to produce their particular legal effects considering its internormativas relations regarding social reality, so that it can achieve the purpose for which it was created. It is not always easy to enforce what has been written, demonstrating a latent imbalance of constitutional rule with reality